Os errantes do cinema marginal - Adriane Maria Puresa Fonseca (2012)
Study on the concept of wandering in the Cinema Marginal, which occurred in Brazil in the late 1960's and early 1970's, appearing with recurrence in the construction of the characters, the narrative and the reception of the film by the viewer. In addition, the study also analyzes the influence of the work of Brecht and Eisenstein in the construction of this concept in the films produced in this period, and the legacy of this movement to the contemporary cinema.